Enchantment : awakening wonder in an anxious age - May, Katherine (Riverhead Books, 2023)
"From the New York Times bestselling author of Wintering, an invitation to rediscover the feelings of awe and wonder available to us all. Many of us feel trapped in a grind of constant change: rolling news cycles, the chatter of social media, our families split along partisan lines. We feel fearful and tired, on edge in our bodies, not quite knowing what has us perpetually depleted. For Katherine May, this low hum of fatigue and anxiety made her wonder what she was missing. Could there be a different way to relate to the world, one that would allow her feel more rested and at ease, even as seismic changes unfold on the planet? Might there be a way for all of us to move through life with curiosity and tenderness, sensitized to the subtle magic all around? In Enchantment, May invites the reader to come with her on a journey to reawaken our innate sense of wonder and awe. With humor, candor, and warmth, she shares stories of her own struggles with work, family, and the aftereffects of pandemic, particularly the feelings of overwhelm as the world rushes to reopen. Craving a different way to live, May begins to explore the restorative properties of the natural world, moving through the elements of earth, water, fire, and air, and identifying the quiet traces of magic that can be found only when we look for them. Through deliberate attention and ritual, she unearths the potency and nourishment that come from quiet reconnection with our immediate environment. Blending lyricism and storytelling, sensitivity and empathy, Enchantment invites each of us to open the door to human experience in all its sensual complexity, and to find the beauty waiting for us there"--